Polarity of motility systems in Myxococcus xanthus - Mauriello, Emilia M.F. (2007)
Myxococcus xanthus is a gliding bacterium that contains two motility systems: S-motility, powered by polar type IV pili, and A-motility, powered by uncharacterized motors and adhesion complexes. The localization and coordination of the two motility engines is essential for directed motility as cells move forward and reverse. During cell reversals, the polarity and localization of motility proteins are rapidly inverted, rendering this system a fascinating example of dynamic protein localization.